UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENANGKAL BAHAYA ALIRAN RADIKALISME YANG BERORIENTASI MENGANCAM SISWA (studi kasus di Lingkungan Pondok Pesantren Ngalah Sengon Agung) - firdausiyah, luluk (Peneliti.net, 2023)
The purpose of the study was to determine the efforts of PAI teachers in countering radicalism. The role of PAI teachers in educating their students has a very large effect, but the reality on the ground is still very minimal. Problems internally in education are still theoretical. Islamic religious education is used as a lesson to be memorized, debated or discussed in its study. Though the most important education is the values ​​contained in the lesson itself. That is what causes students' moral values ​​to have not been able to implement the understanding of Islamic education. Education has a role to prevent the dangers of radicalism. through Islamic Religious Education and efforts on how teachers can indoctrinate the teachings of Islamic Religious Education into the psychology of students to anticipate or prevent the entry of radicalism. naturalistic qualitative methods, techniques in data collection, namely using interviews, observation, and documentation studies. From the research results, PAI teachers' efforts to ward off radicalism are First, Spiritual Education. Second, providing awareness of the importance of science, third, instilling the values ​​of faith and piety. Fourth, provide aswaja education.